A starlet's secret to a sensational afterlife - Kulper, Kendall (Holiday House, 2023)
In 1930s Hollywood, eighteen-year-old budding starlet Henrietta and her handsome-but-moody co-star Declan go from bitter enemies to reluctant partners when they become entangled in the disappearance of a beautiful young actress.